2020
DOI: 10.30892/gtg.29214-489
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Contribution of Tourism on Economic Growth in South African Provinces: A Panel Analysis

Abstract: Ge eo oJ Jo ou ur rn na al l o of f T To ou ur ri is sm m a an nd d G Ge eo os si it te es s Year X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In other terms, people working in tourism-related occupations are more prone to establish positive perceptions and perceptions about their benefits and to have less worry about the detrimental effects of tourism development. Many other reports, such as Tohmo, 2018;Garidzira and Pasara, 2020;Li et al, 2005;Hwang and Lee, 2015;Song et al, 2012;Gozgor and Ongan, 2017;Song and Li, 2008, reported similar facts. It may also be concluded that the larger the economic reliance on tourism, the more likely it is for people to see the beneficial results of tourism.…”
Section: Introductionsupporting
confidence: 59%
“…In other terms, people working in tourism-related occupations are more prone to establish positive perceptions and perceptions about their benefits and to have less worry about the detrimental effects of tourism development. Many other reports, such as Tohmo, 2018;Garidzira and Pasara, 2020;Li et al, 2005;Hwang and Lee, 2015;Song et al, 2012;Gozgor and Ongan, 2017;Song and Li, 2008, reported similar facts. It may also be concluded that the larger the economic reliance on tourism, the more likely it is for people to see the beneficial results of tourism.…”
Section: Introductionsupporting
confidence: 59%
“…For instance, if the variables are stationary at levels, a panel least square is estimated while if the variables are of different level; levels and first difference then a Panel Autoregressive Distributive Lag is deemed fit [26]. In the event that the variables are integrated at first difference, a Panel -VAR or Panel -VECM is appropriate [27]. Since the panel unit root tests indicate a combination of zero and one a Panel Autoregressive Distributive Lag under the Pooled Mean Group is deemed fit (Table 3).…”
Section: Panel Unit Root Testmentioning
confidence: 99%
“…Sport tourism, however, is described in this paper as all types of passive and active participation in sporting activity, involved casually or in an organized manner for business reasons that require travel from home and work locations (Standeven and De Knop, 1999: 12). Nyikana and Tichaawa (2020) seeks to examine the nature of sport and tourism interrelationships in Central Africa, using Cameroon as a case study area. The key findings indicate that the interrelationships between sport and tourism in this context are relatively weak, especially at the policy and planning levels, despite there being potential for strengthening of these at the local operational level for sustainable tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%